Assessment of Aqueous Lithium-based Salt Solutions as Working Fluid for Absorption Chillers using Aspen Plus - Adonis P. Adonardo; Allan N Soriano; Vergel C Bungay (ASEAN Journal of Chemical Engineering, 2017)
Absorption chillers are a viable option for providing waste heat-powered cooling or refrigeration, thereby improving overall energy efficiency-less primary energy input, lower emissions, and cost savings. This study focuses on the assessment of aqueous lithium-based salt solutions as working fluid for absorption chiller in exploring the possibility of developing new mixtures for absorption chillers to improve the performance of the absorption refrigeration systems (ARSs). In this paper, the coefficient of performance (COP) of a single effect absorption chiller using aqueous lithium-based salt solutions (LiF-H2O, LiCl-H2O, LiBr-H2O, and LiI-H2O) as working fluid was assessed using Aspen Plus®. The simulation results obtained showed that the mass and energy were well balanced for all systems. Furthermore, a direct proportionality relationship between COP of absorption chillers and the van't Hoff factor, i of dissociated aqueous salt solutions was observed. The highest COP value is 0.8930 for LiI-H2O among others.